Probing the roles of developmentally active neurons, in early-life adversity induced disruptions of adult behaviors - Weber, Ryan; Mortazavi, Ali; Baram, Tallie Z.; Floriou-Servou, Amalia (Frontiers in Neuroscience, 2025)
Early life adversity (ELA) is associated with subsequent mental health problems, and animal studies provide evidence for a causal role of ELA in the risk for mental illness, including persistent brain changes at molecular, cellular, network and functional levels. As enduring changes in cell function depend on orchestrated expression of genes, a robust body of research has focused on identifying the specific epigenetic and transcriptional programs through which ELA might induce brain changes. These studies have highlighted that the effects of ELA vary by brain region, cell-types and sex. Yet, while major advances were made in the past decade, the precise mechanisms through which ELA shapes the maturation and function of brain cells and their incorporation into circuits remain incompletely understood. Here, we discuss human and animal studies that focus on ELA-induced changes of the epigenome and transcriptome and explore recent technological advances that allow visualization and manipulation of neurons activated during ELA, at later stages of life. One such technology, Targeted Recombination in Active Populations (TRAP), enables precise and permanent genetic access to cells activated during specific sensitive developmental periods. Coupled with the appropriate tools, TRAP can be used to identify cellular transcriptional programs that are altered by the ELA experience in specific cell types and circuits, impacting cognitive and emotional brain functions enduringly. Understanding how ELA changes gene expression, circuit integration and function of neurons that are engaged by ELA will advance our understanding of the mechanisms employed by ELA to heighten the risk for mental illness later in life.